2022
DOI: 10.1002/jsfa.12044
|View full text |Cite
|
Sign up to set email alerts
|

Anti‐adipogenic activities of pheophorbide a and pyropheophorbide a isolated from wild bitter gourd (Momordica charantia L. var. abbreviata Seringe) in vitro

Abstract: BACKGROUND: The wild bitter gourd (WBG) is a commonly consumed vegetable in Asia that has antioxidant and hypoglycemic properties. The present study aimed to investigate the anti-adipogenic activities of isolated compounds from WBG on 8-day differentiated cultures of 3 T3-L1 adipocytes that were then stained with Oil Red O (ORO) or diamidino-2-phenylindole (DAPI).RESULTS: ORO stains of the methanol extracts of de-seeded HM86 cultivar of WBG (WBG-M) and the ethyl acetate fractions (WBG-M-EA) showed anti-adipoge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
0
0
0
Order By: Relevance
“…Furthermore, both SFN and Chlo.a supplementation increased liver oxidative stress but counterbalanced this with an increase in SOD activity. Although some studies have reported the anti-obesogenic potential of SFN [17,[22][23][24] or Chlo.a [28][29][30][31][32], in the present study, these effects are not as evident.…”
Section: Discussioncontrasting
confidence: 82%
See 1 more Smart Citation
“…Furthermore, both SFN and Chlo.a supplementation increased liver oxidative stress but counterbalanced this with an increase in SOD activity. Although some studies have reported the anti-obesogenic potential of SFN [17,[22][23][24] or Chlo.a [28][29][30][31][32], in the present study, these effects are not as evident.…”
Section: Discussioncontrasting
confidence: 82%
“…Chlorophyll compounds have been reported to present some bioactive activities such as, anti-oxidant, anti-cancer, anti-inflammatory, neuroprotective effects, among others [27]. Furthermore, it has been reported that chlorophyll a (Chlo.a), the most abundant photosynthetic pigment, together with its derivatives, has potential antiobesogenic actions in both in vitro and in vivo studies [28][29][30][31][32]. Wang and colleagues [32] demonstrated that the addition of chlorophyll extracts decreased the release rate of free fatty acids and changed the fatty acid composition of soybean oil emulsions at the gastrointestinal system level using an in vitro simulation.…”
Section: Introductionmentioning
confidence: 99%